You are on page 1of 1

1.

a) 𝐷𝑓 = {(𝑥, 𝑦): (𝑥, 𝑦) ∈ ℜ, 𝑥 2 − 1 ≥ 0}, 𝑅𝑓 = {𝑓(𝑥, 𝑦): 𝑓(𝑥, 𝑦) ∈ ℜ}


b) 𝐷𝑓 = {(𝑥, 𝑦): (𝑥, 𝑦) ∈ ℜ}, 𝑅𝑓 = {𝑓(𝑥, 𝑦): 𝑓(𝑥, 𝑦) ∈ ℜ}
c) 𝐷𝑓 = {(𝑥, 𝑦): (𝑥, 𝑦) ∈ ℜ}, 𝑅𝑓 = {𝑓(𝑥, 𝑦): 0 ≤ 𝑓(𝑥, 𝑦) ≤ 2}
d) 𝐷𝑓 = {(𝑥, 𝑦): (𝑥, 𝑦) ∈ ℜ, 𝑥 3 − 𝑦 ≠ 0}, 𝑅𝑓 = {𝑓(𝑥, 𝑦): 𝑓(𝑥, 𝑦) ≠ 0}
e) 𝐷𝑓 = {(𝑥, 𝑦): (𝑥, 𝑦) ∈ ℜ, 𝑥 2 𝑦 2 − 5 > 0}, 𝑅𝑓 = {𝑓(𝑥, 𝑦): 𝑓(𝑥, 𝑦) ∈ ℜ}
f) 𝐷𝑓 = {(𝑥, 𝑦, 𝑧): (𝑥, 𝑦, 𝑧) ∈ ℜ}, 𝑅𝑓 = {𝑓(𝑥, 𝑦, 𝑧): 𝑓(𝑥, 𝑦, 𝑧) > 0}

2.
a) 𝐷𝑓 = {(𝑥, 𝑦): (𝑥, 𝑦) ∈ ℜ, 𝑦 ≥ 0}, 𝑅𝑓 = {𝑓(𝑥, 𝑦): 𝑓(𝑥, 𝑦) ∈ ℜ}
b) 𝐷𝑓 = {(𝑥, 𝑦): (𝑥, 𝑦) ∈ ℜ, 𝑦 + 4 ≥ 0}, 𝑅𝑓 = {𝑓(𝑥, 𝑦): 𝑓(𝑥, 𝑦) ≥ 0}
c) 𝐷𝑓 = {(𝑥, 𝑦): (𝑥, 𝑦) ∈ ℜ, 𝑦 2 − 4 ≥ 0}, 𝑅𝑓 = {𝑓(𝑥, 𝑦): 𝑓(𝑥, 𝑦) ∈ ℜ}
d) 𝐷𝑓 = {(𝑥, 𝑦): (𝑥, 𝑦) ∈ ℜ, 𝑥 − 𝑦 2 ≥ 0}, 𝑅𝑓 = {𝑓(𝑥, 𝑦): 𝑓(𝑥, 𝑦) ≥ 0}
e) 𝐷𝑓 = {(𝑥, 𝑦): (𝑥, 𝑦) ∈ ℜ, 𝑥𝑦 + 2 ≠ 0}, 𝑅𝑓 = {𝑓(𝑥, 𝑦): 𝑓(𝑥, 𝑦) ≠ 0}
f) 𝐷𝑓 = {(𝑥, 𝑦): (𝑥, 𝑦) ∈ ℜ, 𝑦 ≥ 0, 𝑥√𝑦 ≠ 0}, 𝑅𝑓 = {𝑓(𝑥, 𝑦): 𝑓(𝑥, 𝑦) ≠ 0}
g) 𝐷𝑓 = {(𝑥, 𝑦): (𝑥, 𝑦) ∈ ℜ, sin𝑥𝑦 ≠ 0}, 𝑅𝑓 = {𝑓(𝑥, 𝑦): 𝑓(𝑥, 𝑦) ≤ −1, 𝑓(𝑥, 𝑦) ≥ 1}
h) 𝐷𝑓 = {(𝑥, 𝑦): (𝑥, 𝑦) ∈ ℜ}, 𝑅𝑓 = {𝑓(𝑥, 𝑦): −1 ≤ 𝑓(𝑥, 𝑦) ≤ 1}
i) 𝐷𝑓 = {(𝑥, 𝑦): (𝑥, 𝑦) ∈ ℜ}, 𝑅𝑓 = {𝑓(𝑥, 𝑦): −2 ≤ 𝑓(𝑥, 𝑦) ≤ 2}
j) 𝐷𝑓 = {(𝑥, 𝑦): (𝑥, 𝑦) ∈ ℜ, 𝑥 + 𝑦 > 0}, 𝑅𝑓 = {𝑓(𝑥, 𝑦): 𝑓(𝑥, 𝑦) ∈ ℜ}
k) 𝐷𝑓 = {(𝑥, 𝑦): (𝑥, 𝑦) ∈ ℜ}, 𝑅𝑓 = {𝑓(𝑥, 𝑦): 𝑓(𝑥, 𝑦) > 0}

3.
a) 𝐷𝑓 = {(𝑥, 𝑦, 𝑧): (𝑥, 𝑦, 𝑧) ∈ ℜ}, 𝑅𝑓 = {𝑓(𝑥, 𝑦, 𝑧): 𝑓(𝑥, 𝑦, 𝑧) ≥ 0}
b) 𝐷𝑓 = {(𝑥, 𝑦, 𝑧): (𝑥, 𝑦, 𝑧) ∈ ℜ}, 𝑅𝑓 = {𝑓(𝑥, 𝑦, 𝑧): 𝑓(𝑥, 𝑦, 𝑧) ≤ 0}
c) 𝐷𝑓 = {(𝑥, 𝑦, 𝑧): (𝑥, 𝑦, 𝑧) ∈ ℜ, 𝑧 > 0}, 𝑅𝑓 = {𝑓(𝑥, 𝑦, 𝑧): 𝑓(𝑥, 𝑦, 𝑧) ∈ ℜ}
d) 𝐷𝑓 = {(𝑥, 𝑦, 𝑧): (𝑥, 𝑦, 𝑧) ∈ ℜ, 𝑥 2 + 𝑦 2 + 𝑧 2 ≠ 0}, 𝑅𝑓 = {𝑓(𝑥, 𝑦, 𝑧): 𝑓(𝑥, 𝑦, 𝑧) ≠ 0}
e) 𝐷𝑓 = {(𝑥, 𝑦, 𝑧): (𝑥, 𝑦, 𝑧) ∈ ℜ, 9 − 𝑥 2 − 𝑦 2 − 𝑧 2 > 0}, 𝑅𝑓 = {𝑓(𝑥, 𝑦, 𝑧): 𝑓(𝑥, 𝑦, 𝑧) ∈ ℜ}